From Crisis to Resilience: Lessons on Health Services, Financing, and Information Systems in the Philippines - Delos Santos, Maricris; Alampay, Erwin; Rye, Ranjit (Jurnal Transformative, 2026)
This study introduces scientific novelty through an integrated analysis of four core pillars of the health system—service delivery, financing, health workforce, and information systems—which have often been examined separately, utilizing the COVID-19 pandemic as a 'critical event' lens (Das, 1995). Through a qualitative review of Philippine policies (2019–2025), this research successfully uncovers latent structural vulnerabilities that remain invisible under normal operating conditions. The findings reveal a recurring governance dilemma: centralized direction is effective for standard-setting and resource authorization, but counterproductive when intervening in the operational decisions of local government units (LGUs). This condition is further exacerbated by weak local fiscal readiness and poor health data interoperability. The policy implications of this study emphasize the urgency of transformative institutional reforms, including a clearer assignment of functions across all levels of LGUs, the codification of emergency budget flexibility, and the strengthening of national data system integration. Furthermore, the study recommends the formal integration of pandemic risks into the national Disaster Risk Management framework to foster adaptive health governance.